2022
DOI: 10.3390/brainsci12101322
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from M2 Macrophages Improve Angiogenesis and Functional Recovery after Spinal Cord Injury through HIF-1α/VEGF Axis

Abstract: Exosomes are nano-sized vesicles that contain a variety of mRNAs, miRNAs, and proteins. They are capable of being released by a variety of cells and are essential for cell–cell communication. The exosomes produced by cells have shown protective benefits against spinal cord damage (SCI). Recently, it was discovered that M2 macrophages aid in the angiogenesis of numerous illnesses. However, the functional role of M2 macrophage-derived exosomes on SCI is unclear. Here, we investigate the pro-angiogenesis of M2 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…For the first time, our study confirms OPN’s proangiogenic role after SCI in animal models, as evidenced by the revocation of CD31 immunofluorescent signal enhancement after SCI in OPN knockdown mice. OPN could promote angiogenesis through VEGF and/or AKT pathways, 40,41 as we detected potential modulation of VEGF and AKT phosphorylation mediated by OPN post-SCI in this study. Other underlying mechanisms for OPN’s neuroprotective role may include suppressing inflammation and apoptosis through AKT activation 42 .…”
Section: Discussionsupporting
confidence: 54%
“…For the first time, our study confirms OPN’s proangiogenic role after SCI in animal models, as evidenced by the revocation of CD31 immunofluorescent signal enhancement after SCI in OPN knockdown mice. OPN could promote angiogenesis through VEGF and/or AKT pathways, 40,41 as we detected potential modulation of VEGF and AKT phosphorylation mediated by OPN post-SCI in this study. Other underlying mechanisms for OPN’s neuroprotective role may include suppressing inflammation and apoptosis through AKT activation 42 .…”
Section: Discussionsupporting
confidence: 54%
“…For example, Huang et al. revealed that MEs improved angiogenesis after spinal cord injury (SCI) by enhancing the expression of pro-angiogenesis factors (HIF-1α and VEGF) [ 41 ]. Similarly, another study showed that MEs stimulated the angiogenic activities of microvascular endothelial cells in vitro , thereby promoting revascularization after SCI [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in a high-glucose microenvironment, FM hydrogel and the released M2-Exo exhibited a synergistic effect in inducing M2 macrophages, which resulted in a significant enhancement of angiogenic behaviors in HUVECs, including proliferation, migration, angiogenesis, and scratch healing ability, through a paracrine mechanism. M2 macrophages are known to constitutively express VEGF, which allowed them to interfere with various stages of the angiogenesis cascade, including promoting endothelial cells proliferation, sprouting, and the formation of neovascular networks. The in vitro findings supported the role of M2 macrophages in enhancing angiogenesis. In vivo, the M2 macrophages induced by FM-Exo hydrogel secreted abundant VEGF in the wound site, facilitating the sprouting and elongating of blood vessels from existing vessels toward the wound.…”
Section: Resultsmentioning
confidence: 83%